Internalization Of Moral Values In Children Through Prophetic-Based Education In The Digital Era - Nurul Ismaiyah; Winda Syafaatin Maulidah (LP3M STAI MA'ARIF MAGETAN, 2023)
Internalization of moral values through prophetic based education in the digital era is education that makes the prophet Muhammad Saw a role model. Very important to set an example for the prophet Muhammad Saw trough the habit of knowing his character and personality. prophetic education is done because early childhood learns through imitating what happens in the surrounding environment which becomes a habit. The type of research used in this paper is library research, namely a series of studies that are explored through various information such as books, encyclopedias, newspapers, magazines or previous research and documents. The result of this study indicate that the internalization of moral values through prophetic education is carried out through several activities such as introducing monotheism to children by getting used to saying the Syahadat and La ilaha illallah, introduce Muhammad's wisdom, imitate the four characteristics of the prophet who is shiddiq Amanah Tabligh and Fathonah, get use to carrying out prayers independently, studying the Qur'an with interesting learning methods and giving rewards as an appreciation to children who istiqomah to overcome.